The eco-innovation approach for the sustainability of railroads in the South of the state of Santa Catarina - Colonetti, Ricardo Alves; Yamaguchi, Cristina Keiko; Vieira, Adriana Carvalho Pinto; Zilli, Julio Cesar Farias (Sustainability in Debate, 2016)
The article seeks to find how eco-innovation can contribute to the sustainability of the railroads operating in the Southern part of the state of Santa Catarina. It displays the findings of a descriptive and bibliographical research, with a qualitative approach and based on a case study. A questionnaire was applied to the project and transportation maintenance manager of the railroad company Ferrovia Tereza Cristina S.A. The manufacturing and the use of the eco-wagon caused several benefits in the economic, environmental and social fields. There was a 15 percent reduction of operational costs; the useful life of the eco-wagon tripled; cargo transportation capacity increased by 1.5 tons per car; the time for cargo unloading was shortened from five to three minutes; the level of noise during unloading was reduced by the use of recycled materials; the risk of contamination by leakage during transportation was reduced; the need to cut down two trees per wagon was eliminated by the use of recycled materials.